ANALISIS KESULITAN SISWA MTS PADA MATERI BANGUN RUANG SISI DATAR - Rida Siti Saripah; Aflich Yusnita Fitrianna (IKIP Siliwangi, 2021)
This research was conducted with the aim of analyzing students' difficulties in the material on the flat side. Using a qualitative descriptive research method with samples from this study, 10 students of class VIII MTs Darul Falah for the 2020-2021 academic year. For data collection using instruments in the form of 5 items that have been adjusted to the indicators. Furthermore, student answers are analyzed to find out student errors based on predetermined indicators. Of the five indicators, there are three indicators belonging to the highest level of difficulty, namely the indicator for calculating the volume of the prism, the indicator for analyzing problems related to the volume of the pyramid and the indicator for analyzing problems related to the area of the beam. The percentages are 81.63%, 91.83% and 79%, respectively. With the following error factors: (1) memorizing the formula without understanding the concept of solving the problem; (2) the difficulty of students in sketching problem solving; (3) students' carelessness in calculating math problems; (4) students' lack of accuracy in solving mathematical problems.